Stereological analysis of metanephros from domestic cat (Felis catus, Linnaeus 1798) embryos and fetus. (24th September 2021) - Paretsis, Barbara Fidalgo; Mario, Lara Carolina; Sasahara, Tais Harumi de Castro; da Silva, Liege Cristina Garcia; dos Santos, José Manoel; Kfoury Júnior, José Roberto; Leandro, Rafael Magdanelo
Abstract: Kidney diseases are the most common illness for cats with a prevalence seven times higher than in dogs. Metanephros is the last of three renal systems to be formed during the embryonic period, which then becomes the permanent kidney. The current work aimed to analyse the morphology and to quantify the structures present in the development of metanephros from domestic cat ( Felis catus ) embryos and foetuses. For this purpose, the evaluation of the biometric parameters of metanephros from cat embryos and foetuses was performed in addition to the quantification of renal corpuscles and volume of cortical and medullary layers by stereological analysis. The evaluated biometric parameters were weight, width, height, thickness and volume. The values of the measured biometric parameters increased throughout the gestational stages. The quantity of renal corpuscles gradually increased following the embryo‐foetal development, mainly during the middle of the gestational stage. It was during this phase that morphologically, a complete corticomedullary division was observed. Although the difference in the quantity of renal corpuscles between the middle and the end of the gestational stages was not statistically significant, there was an increase in the volume of the medullary layer and a decrease in the volume of the cortical layer between these two stages. These findings suggest that the metanephros presents a progressive growth with the renal corpuscles following this development until the middle of the gestational stage. Starting from this phase, the differentiation of the corticomedullary layers can be seen with a significant increase in the medullary layer.